Project of Reconstruction of a Hostel under a Apartment Residential Building of a Rental Type in the City of Minsk - Viktorovna, Shanyukevich Irina; Valentinovna, Guzarevich Yanina (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents a project for the reconstruction of a dormitory on the basis of a technical expertise for a multi-apartment residential building in Minsk with the addition of an additional sixth floor, the installation of elevator equipment and the placement of office premises on the ground floor with separate entrances, as well as a comparison of the amount of income from payment for use of residential premises in the hostel and residential premises of the rental type after the proposed reconstruction.